A comparison of frontal theta activity during shooting among biathletes and cross-country skiers before and after vigorous exercise - Luchsinger, H.; Sandbakk, O.; Schubert, M.; Ettema, G.; Baumeister, J. (PLOS ONE, 2016)
Previous studies using electroencephalography (EEG) to monitor brain activity have linked higher frontal theta activity to more focused attention and superior performance in goal-directed precision tasks. In biathlon, shooting performance requires focused attention after high-intensity cross-country skiing. Purpose: To compare biathletes (serving as experts) and cross-country skiers (novices) and examine the effect of vigorous exercise on frontal theta activity during shooting. Methods: EEG frontal theta (4-7 Hz) activity was compared between nine biathletes and eight cross-country skiers at comparable skiing performance levels who fired 100 shots on a 5-m indoor shooting range in quiescent condition followed by 20 shots after each of five 6-min high-intensity roller skiing sessions in the skating technique on a treadmill. Results: Biathletes hit 80±14% and 81±10% before and after the roller skiing sessions, respectively. For the cross-country skiers these values were significantly lower than for the biathletes and amounted to 39±13% and 44±11% (p<0.01). Biathletes had on average 6% higher frontal theta activity during shooting as compared to cross-country skiers (F1,15 = 4.82, p = 0.044), but no significant effect of vigorous exercise on frontal theta activity in either of the two groups were found (F1,15 = 0.14, p = 0.72). Conclusions: Biathletes had significantly higher frontal theta activity than cross-country skiers during shooting, indicating higher focused attention in biathletes. Vigorous exercise did not decrease shooting performance or frontal theta activity during shooting in biathletes and cross-country skiers.